2015
DOI: 10.1016/j.jmaa.2014.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Products of composition, multiplication and radial derivative operators from logarithmic Bloch spaces to weighted-type spaces on the unit ball

Abstract: Let H(B) denote the space of all holomorphic functions on the unit ball B of C n , ψ ∈ H(B) and ϕ be a holomorphic self-map of B. Let C ϕ , M ψ and R denote the composition, multiplication and radial derivative operators, respectively. In this paper, we characterize the boundedness and compactness of linear operators induced by products of these operators from logarithmic Bloch spaces to weighted-type spaces on the unit ball.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…For more information about the radial derivative operator we refer to [11,12] and the references therein. Using radial derivative operator and φ 1 , φ 2 , φ 3 ∈ H(B m ), Liu and Yu in [13] studied the extension of the operator T φ 1 ,φ 2 ,ξ which is denoted by T φ 1 ,φ 2 ,φ 3 ,ξ and defined as…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For more information about the radial derivative operator we refer to [11,12] and the references therein. Using radial derivative operator and φ 1 , φ 2 , φ 3 ∈ H(B m ), Liu and Yu in [13] studied the extension of the operator T φ 1 ,φ 2 ,ξ which is denoted by T φ 1 ,φ 2 ,φ 3 ,ξ and defined as…”
Section: Introductionmentioning
confidence: 99%
“…In particular, by setting φ 2 (z) ≡ φ 3 (z) ≡ 0, the operator T φ 1 ,φ 2 ,φ 3 ,ξ get reduced to W φ 1 ,ξ . Similarly, for φ 1 (z) ≡ φ 3 (z) ≡ 0, the operator T φ 1 ,φ 2 ,φ 3 ,ξ get reduced to W φ 2 ,ξ R. The above defined operator can be found in [13] and the references therein. Various product-type operators have been studied for spaces of analytic functions on the unit disk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ψ n }. The sum operator for n = 1 has been studied in several papers, see [10][11][12][17][18][19][20]. Recall that the Bell polynomial for n, k ∈ N 0 is defined as…”
Section: Introductionmentioning
confidence: 99%
“…In [1], Attele showed that the Hankel operator H f is bounded on the Bergman space A 1 if and only if f ∈ LB, where H f = (I − P)( f ), I is the identity operator and P is the Bergman projection from L 1 into A 1 . See, for example, [3,6,11,17,26,27,29] for some results on logarithmic spaces and operators on them.…”
Section: Introductionmentioning
confidence: 99%